2011
DOI: 10.1074/jbc.m111.309252
|View full text |Cite
|
Sign up to set email alerts
|

Correct End Use during End Joining of Multiple Chromosomal Double Strand Breaks Is Influenced by Repair Protein RAD50, DNA-dependent Protein Kinase DNA-PKcs, and Transcription Context

Abstract: Background: Incorrect end use during repair can cause chromosome rearrangements. Results: DNA-PKcs and RAD50 limit incorrect end use, and a break downstream from an active promoter shows elevated incorrect end use; these factors and conditions have distinct effects on repair requiring end processing. Conclusion: DNA-PKcs, RAD50, and transcription context influence correct end use. Significance: Correct end use and end processing appear distinct processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(111 citation statements)
references
References 70 publications
7
104
0
Order By: Relevance
“…4C. A similar result was also using a second inducible DSB system in a U2OS cell line carrying the EJ5-GFP reporter (23), where CTCF is also recruited to most sites flanking the I-Sce I induced break point (Fig. 4D).…”
Section: Ctcf Prevents Genomic Instabilitysupporting
confidence: 62%
See 1 more Smart Citation
“…4C. A similar result was also using a second inducible DSB system in a U2OS cell line carrying the EJ5-GFP reporter (23), where CTCF is also recruited to most sites flanking the I-Sce I induced break point (Fig. 4D).…”
Section: Ctcf Prevents Genomic Instabilitysupporting
confidence: 62%
“…To obtain more direct evidence supporting the interaction of CTCF at sites of DNA damage, we investigated whether CTCF interacts with the DNA near DSB ends by ChIP in a U2OS cell line carrying the DR-GFP reporter (23,24) (Fig. S3C).…”
Section: Ctcf Prevents Genomic Instabilitymentioning
confidence: 99%
“…We used human U2OS cells (provided by J. Bartek, Institute of Cancer Biology and Centre for Genotoxic Stress Research), U2OS DR-GFP (provided by M. Jasin, Sloan-Kettering Institute) and U2OS SA-GFP cells (described in ref. 34). We cultured all cells lines in DMEM (Invitrogen) supplemented with 10% (vol/vol) FCS (Eurobio), 100 U/ml penicillin and 100 μg/ml streptomycin (Invitrogen) in a humidified atmosphere with 5% CO 2 at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…We followed exactly the same protocol to estimate single-strand annealing using U2OS SA-GFP cells that were established previously. 34 Antibodies. Primary antibodies used during immunoblot (IB) or immunofluorescence (IF) experiments are listed below.…”
Section: Supplemental Materialsmentioning
confidence: 99%
“…To assess the functional relevance of the observed preferential recruitment of DROSHA to NHEJ-prone AsiSI sites, we exploited the U2OS EJ5 cellular system, a well-established GFP-based reporter cell system in which the reconstitution of a functional GFP gene occurs after DNA damage generation and repair by NHEJ repair (Gunn et al, 2011), (Gunn and Stark, 2012) (see cartoon in Figure 5A). Interestingly, we observed that the number not peer-reviewed) is the author/funder.…”
Section: Drosha Controls Dna Repair By Nhejmentioning
confidence: 99%